Curcumin-loaded chitosan–bovine serum albumin nanoparticles potentially enhanced Aβ 42 phagocytosis and modulated macrophage polarization in Alzheimer’s disease - Rui Yang; Yan Zheng; Qingjun Wang; Liang Zhao (Nanoscale Research Letters, 2018)
Abstract Alzheimer’s disease (AD) is the most common neurodegenerative disorder in the elderly population. In the treatment of AD, some obstacles, including drug penetration difficulty through the blood–brain barrier (BBB), inadequate clearance of the Aβ peptide, and the massive release of inflammatory factors, must be urgently overcome. To solve these problems, we developed special and novel nanoparticles (NPs) made of chitosan (CS) and bovine serum albumin (BSA) to enhance the penetration of drugs through the BBB. Curcumin as a potent anti-inflammatory agent was used to increase the phagocytosis of the Aβ peptide. The results demonstrated that curcumin-loaded CS-BSA NPs effectively increased drug penetration through the BBB, promoted the activation of microglia, and further accelerated the phagocytosis of the Aβ peptide. Furthermore, curcumin-loaded CS-BSA NPs inhibited the TLR4-MAPK/NF-κB signaling pathway and further downregulated M1 macrophage polarization. This study suggested that curcumin-loaded CS-BSA NPs hold the potential to enhance Aβ 42 phagocytosis through modulating macrophage polarization in AD.